5 parasitic nematodes species (Nematoda: Oxyurida, Thelastomatoidea) in the mole-criket (Gryllotalpa africana) of Vietnam - Luc, Pham Van (Academia Journal of Biology, 2012)
Studying of parasitc nematodes on invertebrate animals, also including insects has been made for about 20 years ago in Vietnam, such as mole-criket, earthworm, myriapod, cockroach, etc. In this study, total about 200 individuals of mole-criket (Gryllotalpa africana) were examined for nematodes parasitic. The mole-criket were catched from ricefield in some provinces of the Northern Vietnam (Hanoi and Lai Chau). Using the Skrjabin’s method to collect parastic nematodes. Preservation of nematodes specimens in 4-6% formaline solution. The nematode specimens were described and measured with a Zeiss Axyolab Microscope (Germany) and Olympus CH40 Microscope (Japan). Preserving this specimens in Institude of Parasitology, Russian Academy of Science, Matxcova. Thelastomatoidea, usually is called pinworm, is one of two superfamily belonging to Oxyurida order. Their adult stage live in invertebrate animals, mainly arthropod. This nematodes group is not related with the Oxyuroidea which parasiting on vertebrate animals. The superfamily has received little attention from different systematic researchers in the world, for example Kloss (1960), Skrjabin et al. (1966), Poinar (1977), Adamson & Van Waerebeke (1985), Adamson (1989). Therefore Adamson & Van Waerebeke (1992) has divided this superfamily into 5 family Thelastomatidae, Protrelloididae, Hystrignathidae, Travassosinematidae and Pseudonymidae then considered the systematics before. The results of this article are based on Adamson M.L. & Van Waerebeke D.’s taxonomic system. 5 parasitic nematodes were found from the mole-criket’s intestine and described in this article, including Chitwoodiella ovofilamenta Basir, 1948; Singhiella singhi Rao, 1958; Mirzaiella asiatica Basir, 1942; Indiana coimbutoriensis Latheef & Seshadri, 1972 (Family: Travassosinematidae) and Gryllophila skrjabini (Sergiev, 1923) Basir, 1956 (Family: Thelastomatidae). That is the first time 5 parasitic nematodes species parasiting on invertebrate animals in Vietnam are described.